Community Based Tourism Desa Pangandaran dan Desa Pananjung Dalam Pengembangan Wisata Alam di Kawasan Pantai Pangandaran Jawa Barat - Ria Krisnasari (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2022)
Community-Based Tourism carried out by coastal communities is a concept that needs attention. The community has been able to design and operate optimally all tourism activities according to regional characteristics through productivity test benchmarks (group management) and empowerment tests (ecoliteracy and eco-design). However, empowerment and management are still not maximized, which is a problem that needs attention. Community-Based Tourism Pangandaran Beach needs to get attention from the local government, tourism object managers, and the surrounding community, for the empowerment and welfare of the Pangandaran Beach community. This research uses qualitative research methods, using data collection techniques through observation, interviews, questionnaires, and documentation studies so that the results obtained are Community Based Tourism Development of Pangandaran Beach Nature Tourism, West Java. has increased in terms of the number of traders every year but in terms of income, it is not as good as before being relocated because the reason for the relocation is not representative and the stalls are small in size so that the traders cannot sell optimally. The development of a tourist destination must of course have full support from the local government itself, which is supported by the provincial and central government of West Java, as well as support from various stakeholders, namely Destination Managers, Local Communities, Traders, Hotel Managers and including tourists so that they can support each other. . Each supporting factor must also be maintained so that it continues to develop in a better direction and the inhibiting factors can be taken into account so that they can be minimized.